Effective mitigation of cross-contamination in classroom conditioned by intermittent air jet cooling with use of portable air cleaners. (1st July 2022) - Karam, Jennifer; Katramiz, Elvire; Ghali, Kamel; Ghaddar, Nesreen
Abstract: This work investigated the effect of using portable air cleaners (PACs) in a classroom ventilated by an intermittent air jet system (IAJS) for reducing the risk of cross-contamination. The classroom had two student groups separated by an aisle where the PACs were placed and operated continuously. A 3-D computational fluid dynamic (CFD) model was developed and validated experimentally to predict the complex transient flow field. The spread of contaminants from one group to another ( scenario 1 ) and from one row to another within one group ( scenario 2 ) was evaluated in terms of reaching concentration levels similar to the case implementing the 2-m distancing between students. Two indicators were used; the intake fraction index ( iF ) and an exposure reduction index (ER ) that compared the proposed system to a reference case when the PAC is not used ("No-PAC"). It was found that a PAC flowrate of 350 m 3 /h was able to fulfill the aforementioned criteria for typical IAJS flow rate of 294 l/s and a period of 4.5 min. The proposed system reduced the exposure by 67% for the students sitting in the same group of the infected student and by 87% for the students sitting in the neighboring group compared to the "No-PAC " case. The maximum exposure level of IJAS-PAC system was lower than that obtained with seating distance of 2 m. Furthermore, it was found that operating the PAC at 350 m 3 /h resulted in 3% increase of the energy compared to operation of the IAJS alone. Graphical abstract: Image 1 Highlights: Portable air cleaners (PACs) are used in a classroom with an intermittent air jet system. A CFD model was developed and validated to assess the indoor contaminants' dispersion. The contaminants' concentration were lower than those obtained with the 2 m distancing. PACs at 350 m 3 /h reduced cross-contamination by 67%–87% compared to no PAC case.